CAN STUDENT ASSESSMENT SHEETS REPLACE OBSERVATION SHEETS? - Badrun Kartowagiran; Eka Ary Wibawa; Fitri Alfarisa; Dian Normalitasari Purnama (Jurnal Cakrawala Pendidikan, 2019)
Observation is argued as the most suitable technique to assess the execution of authentic assessment. Unfortunately, it requires great amount of time and money. We need an alternative. Therefore, the purpose of this study was to develop an instrument in the form of a student assessment sheet on the implementation of authentic assessments in Mathematics subjects. This research is a development research that uses standard procedures for developing instruments. The result of the analysis with Aiken’s formula showed that every item of the instrument was in a good category. The result of the analyses using Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA), and Multitrait-Multimethod showed that the instrument had good construct validity. The result of reliability estimation using Cronbach Alpha  (α) also showed that the instrument was in the reliable category. Thus, it can be concluded that the instrument in the form of student assessment sheets for assessing the implementation of authentic assessment in junior high school Mathematics learning is highly valid and reliable, which means that the developed instrument can replace the equivalent observation sheet.